Mortality due to pesticide poisoning in Colombia, 1998-2011 - Chaparro-Narváez, Pablo; Castañeda-Orjuela, Carlos (Biomedica, 2015)
Introduction: Poisoning due to pesticides is an important public health problem worldwide due its morbidity and mortality. In Colombia, there are no exact data on mortality due to pesticide poisoning. Objective: To estimate the trend of mortality rate due to pesticide poisoning in Colombia between 1998 and 2011. Materials and methods: We carried out a descriptive analysis with the database reports of death as unintentional poisoning, self-inflicted intentional poisoning, aggression with pesticides, and poisoning with non-identified intentionality, population projections between 1998 and 2011, and rurality indexes. Crude and age-adjusted mortality rates were estimated and trends and Spearman coefficients were evaluated. Results: A total of 4,835 deaths were registered (age-adjusted mortality rate of 2.38 deaths per 100,000 people). Mortality rates were higher in rural areas, for self-inflicted intentional poisoning, in men and in age groups between 15 and 39 years old. The trend has been decreasing since 2002. Municipality mortality rates due to unintentional poisoning and aggression correlated significantly with the rurality index in less rural municipalities. Conclusions: Mortality rates due to pesticide poisoning presented a mild decrease between 1998 and 2011. It is necessary to adjust and reinforce the measures conducive to reducing pesticide exposure in order to avoid poisoning and reduce mortality.